2014
DOI: 10.3171/2014.7.jns132306
|View full text |Cite
|
Sign up to set email alerts
|

The stereotactic approach for mapping epileptic networks: a prospective study of 200 patients

Abstract: Object Stereoelectroencephalography (SEEG) is a methodology that permits accurate 3D in vivo electroclinical recordings of epileptiform activity. Among other general indications for invasive intracranial electroencephalography (EEG) monitoring, its advantages include access to deep cortical structures, its ability to localize the epileptogenic zone when subdural grids have failed to do so, and its utility in the context of possible multifocal seizure onsets with the need for bihemispheric explorations. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
122
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 31 publications
(45 reference statements)
2
122
4
Order By: Relevance
“…• After subdural grid failure permanent morbidity after evaluation with surface electrodes (3-6%) compared with the use of SEEG electrodes (0-3%) because of the need for craniotomy and invasive grid placement in both adult and pediatric patients (34)(35)(36)(37)42); however, comparisons of surface electrodes and SEEG as well as complication rates have been limited because of differing study indications, methodology, and techniques. Larger studies of SEEG monitoring in pediatric patients have reported that efficacy of seizure foci identification and safety are similar to those reported in studies of adults (22,41,43,44).…”
Section: Stereotactic Electroencephalography (Seeg)mentioning
confidence: 99%
“…• After subdural grid failure permanent morbidity after evaluation with surface electrodes (3-6%) compared with the use of SEEG electrodes (0-3%) because of the need for craniotomy and invasive grid placement in both adult and pediatric patients (34)(35)(36)(37)42); however, comparisons of surface electrodes and SEEG as well as complication rates have been limited because of differing study indications, methodology, and techniques. Larger studies of SEEG monitoring in pediatric patients have reported that efficacy of seizure foci identification and safety are similar to those reported in studies of adults (22,41,43,44).…”
Section: Stereotactic Electroencephalography (Seeg)mentioning
confidence: 99%
“…1,11,12,15,25 Patient registration can be performed in frame-based or frameless conditions. Since the fall of 2008, we have used a robotic assistant in frame-based conditions for implanting all SEEG electrodes at Niguarda Hospital.…”
mentioning
confidence: 99%
“…However, invasive EEG monitoring is sometimes needed in patients with poorly localized, multifocal, or discordant scalp EEG ictal patterns to map seizure onset or in those whose epileptogenic zone is in close proximity to functional cortex to minimize functional deficits following resection. [3][4][5][6][7][8] These EEG techniques invade the brain parenchyma along the trajectories of multiple depth electrodes (stereotactic EEG [SEEG]) and/or cover the cortex with a "foreign body" (subdural grids) and often extend beyond the eventual resection area. Furthermore, greater histopathologic changes are evident in the resected tissue of patients who have undergone invasive EEG monitoring as compared to those who undergo surgical resection without prior monitoring.…”
mentioning
confidence: 99%